How does the break-junction quasiparticle tunnel conductance look like for d-wave superconductors? - Gabovich, A.M.; Voitenko, A.I. (Физика низких температур, 2017)
The bias-voltage, V, dependences of the differential tunnel conductance G(V) = dJ/DV were calculated for the quasiparticle current J flowing in the ab plane across the break junction made of d-wave superconductors. The tunnel directionality effect was taken into account by introducing an effective tunneling cone described by the angle 2θ₀. It was shown that G(V) looks like predominantly d-wave or isotropic s-wave ones, depending on the magnitude of θ₀ and the rotation angles of the crystal lattices of electrodes with respect to the junction plane. In certain configurations, the G(V) dependences of nominally symmetric S-I-S junctions may turn out similar to those for non-symmetric S–I–N junctions (here, S, I, and N denote superconductors, insulators, and normal metals, respectively) and provide misleading information about the actual energy gap. At finite temperatures, sub-gap structures appear, which possess features appropriate to both d- and s-wave superconductors and are dependent on the problem parameters.